Nanosensors and particles: a technology frontier with pitfalls - Viola Vogel (Journal of Nanobiotechnology, 2019)
Abstract As we are approaching 20 years after the US National Nanotechnology Initiative has been announced, whereby most of that funding was spend to engineer, characterize and bring nanoparticles and nanosensors to the market, it is timely to assess the progress made. Beyond revolutionizing nonmedical applications, including construction materials and the food industry, as well as in vitro medical diagnostics, the progress in bringing them into the clinic has been far slower than expected. Even though most of the advances in nanosensor and nanoparticle research and development have been paid for by disease-oriented funding agencies, much of the gained knowledge can now be applied to treat or learn more about our environment, including water, soil, microbes and plants. As the amount of engineered nanoparticles that enter our environment is currently exponentially increasing, much tighter attention needs to be paid to assessing their health risk. This is urgent as the asbestos story told us important lessons how financial interests arising from a rapid build up of a flourishing industry has blocked and is still preventing a worldwide ban on asbestos, nearly 100 years after the first health risks were reported.